Immune–metabolic interactions in homeostasis and the progression to NASH. (October 2022) - Hoogerland, Joanne A.; Staels, Bart; Dombrowicz, David
Abstract : The incidence of non-alcoholic fatty liver disease (NAFLD) has increased significantly over the past two decades. NAFLD ranges from simple steatosis (NAFL) to nonalcoholic steatohepatitis (NASH) and predisposes to fibrosis and hepatocellular carcinoma (HCC). The importance of the immune system in hepatic physiology and in the progression of NAFLD is increasingly recognized. At homeostasis, the liver participates in immune defense against pathogens and in tolerance of gut-derived microbial compounds. Hepatic immune cells also respond to metabolic stimuli and have a role in NAFLD progression to NASH. In this review, we discuss how metabolic perturbations affect immune cell phenotype and function in NAFL and NASH, and then focus on the role of immune cells in liver homeostasis and in the development of NASH. Highlights: The altered metabolic environment in non-alcoholic fatty liver disease (NAFLD) promotes hepatocyte metabolic dysfunction and cellular stress, affecting the highly diverse hepatic immune compartment. Resident macrophages are activated during the early phase of liver injury and disease-promoting metabolic and tissue environmental signals alter their gene expression programs, resulting in identity loss. In a nonalcoholic steatohepatitis (NASH) environment, classical DC and CD8 + T cell populations are altered. CD8 + T cells with an 'exhausted phenotype' are activated and kill hepatocytes, promoting tissue damage. The phenotype and function of hepatic immune cells is reshaped during the progression of NAFL to NASH, but the role of the cellular interactions in disease progression is only starting to be uncovered.